Cybercrimes and Information Crimes: From a Legal and Technical Perspective - Farida Abdelfattah Rady; Sally Awad Elsakka (International Journal of Law Research and Studies, 2024)
Cybercrimes are criminal activities that target computers or networks with the aim of disrupting or damaging them, or using their data in illegal ways. These crimes often include introducing viruses that affect one device and then spread to the rest of the devices on the network, causing a variety of damages. Information crimes, or cybercrimes, and electronic crimes are known as criminal activities committed using computers or any devices connected to the Internet. These crimes aim to illegally access information or damage or disable devices. With the widespread spread of the Internet, cybercrimes have increased significantly, and these crimes are organized by individuals or groups, whether they are beginners or professionals. The primary motive behind cybercrimes is to achieve financial gain, and they are carried out through various means such as ransomware attacks, email fraud, theft of bank accounts and credit cards, and other various forms of these criminal activities. This research deals with cybercrimes and information crimes from a legal perspective supported by technical concepts in an attempt to clarify the types, differences and forms of each.
Keywords: Cybercrimes; Information Crimes; Law; Information Technology